2020
DOI: 10.1021/acsomega.0c00769
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Composition and Interfacial Tension on the Rheology and Morphology of Heavy Oil-In-Water Emulsions

Abstract: Rheological and morphological properties of heavy crude oil-in-water (O/W) emulsions have been studied. Two series of emulsions were considered: first, the surfactant type remained constant, while the continuous phase content was varied and second, the surfactant type was varied while the continuous phase content remained constant. Under stress-controlled shearing, all samples exhibit viscoplastic behavior. The rheological properties are directly related to the morphology of the emulsions which vary in size of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…By lowering the W/O interfacial tension of the system, the presence of Tween 20 (the demulsifier) leads to the formation of smaller droplets during emulsification (see the SI). Since at high Reynolds numbers, the mean droplet size results from a balance between the droplet interfacial and inertial stresses, R 0 scalesfor a given Reynolds numberas γ 3/5 , where γ is the W/O interfacial tension of the system, as experimentally reported . If one considers that R 0 varies with γ, according to this scaling law, it is then straightforward to establish from eq that: .…”
Section: Theoretical Interpretationmentioning
confidence: 84%
See 1 more Smart Citation
“…By lowering the W/O interfacial tension of the system, the presence of Tween 20 (the demulsifier) leads to the formation of smaller droplets during emulsification (see the SI). Since at high Reynolds numbers, the mean droplet size results from a balance between the droplet interfacial and inertial stresses, R 0 scalesfor a given Reynolds numberas γ 3/5 , where γ is the W/O interfacial tension of the system, as experimentally reported . If one considers that R 0 varies with γ, according to this scaling law, it is then straightforward to establish from eq that: .…”
Section: Theoretical Interpretationmentioning
confidence: 84%
“…Since at high Reynolds numbers, the mean droplet size results from a balance between the droplet interfacial and inertial stresses, 18 R 0 scalesfor a given Reynolds numberas γ 3/5 , where γ is the W/O interfacial tension of the system, as experimentally reported. 19 If one considers that R 0 varies with γ, according to this scaling law, it is then straightforward to establish from eq 7 that:…”
Section: ■ Theoretical Interpretationmentioning
confidence: 99%
“…Additionally, the oil/water interfacial tension indicates the velocity and the performance of water spreading. For example, the lower is the interfacial tension, the greater is the extent of spreading (Arinina, Zuev, Kulichikhin, & Malkin, 2020; Gaonkar, 1989). All these parameters above influence the sensorial properties of final emulsions as well as their stability.…”
Section: Effect Of Oil Properties On Emulsion Stabilitymentioning
confidence: 99%
“…It is achieved by altering the emulsifier nature or composition of an aqueous phase and the addition of suitable surfactants forming a thick multilamellar film that adsorbs over the droplet interface (Qadir et al ., 2016). The stability of NE also varies with the rheological behaviour of the emulsions which depends on the ratio of oil and water and the size distribution of the droplets (Arinina et al ., 2020). Pal (2000) reported that concentrated samples of NE mostly exhibit shear‐thinning behaviour and the viscosity of the NE system is determined by droplet size.…”
Section: Formulation Formation and Stability Of Nesmentioning
confidence: 99%